Multidimensional relationships between sensory perception and cognitive aging - Kannan, Lakshmi; Lelo de Larrea-Mancera, Esteban Sebastian; Maniglia, Marcello; Vodyanyk, Mariya M.; Gallun, Frederick J.; Jaeggi, Susanne M.; Seitz, Aaron R. (Frontiers in Aging Neuroscience, 2024)
A growing literature suggests that declines in sensory/perceptual systems predate cognitive declines in aging, and furthermore, they are highly predictive for developing Alzheimer’s disease and Alzheimer’s related dementias (ADRD). While vision, hearing, olfaction, and vestibular function have each been shown to be related to ADRD, their causal relations to cognitive declines, how they interact with each other remains to be clarified. Currently, there is substantial debate whether sensory/perceptual systems that fail early in disease progression are causal in their contributions to cognitive load and/or social isolation or are simply coincident declines due to aging. At the same time, substantial declines in any of these senses requires compensation, can strain other neural processes and impact activities of daily living, including social engagement, quality of life, and the risk of falls. In this perspective piece, we review literature that illustrates the different relationships between sensory/perceptual systems, cognitive aging and ADRD. We suggest that broadly administered and precise assessment of sensory/perceptual functions could facilitate early detection of ADRD and pave the way for intervention strategies that could help reduce the multifaceted risk of developing ADRD and to improve everyday functioning as people age.